The Colored Aristocracy of St. Louis - Clamorgan, Cyprian, 1830-1902 (Book collections on Project MUSE., 1999)
"In 1858, Cyprian Clamorgan wrote a brief but immensely readable book entitled The Colored Aristocracy of St. Louis. The grandson of a white voyageur and a mulatto woman, he was himself a member of the "colored aristocracy." In a setting where the vast majority of African Americans were slaves, and where those who were free generally lived in abject poverty, Clamorgan's "aristocrats" were exceptional people. Wealthy, educated, and articulate, these men and women occupied a "middle ground." Their material advantages removed them from the mass of African Americans, but their race barred them from membership in white society." "The Colored Aristocracy of St. Louis is both a serious analysis of the social and legal disabilities under which African Americans of all classes labored and a settling of old scores. Somewhat malicious, Clamorgan enjoyed pointing out the foibles of his friends and enemies, but his book had a serious message as well. "He endeavored to convince white Americans that race was not an absolute, that the black community was not a monolith, that class, education, and especially wealth, should count for something.""--Jacket.